Pengembangan Sistem Rekam Medis Rumah Sakit dengan Multi User Rest Server berbasis Permissioned Blockchain menggunakan Framework Hyperledger - Ekky Pramudito Setiawan; Adhitya Bhawiyuga; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Storing medical records on paper cause problems that can make medical records data scattered across various healthcare facility. The problems concerning healthcare facility to use electronic medical records so that they can share the data and increase its availability. Data sharing mechanism raises awareness that data privacy and integrity must be guaranteed. A technology that can be utilized for this problems that arise is blockchain. In this research proposed a medical record system using Hyperledger framework based on permissioned blockchain. The proposed system solves this problem by recording transactions that occur on medical records thus providing data integrity. Recorded transactions will be distributed inside blockchain envinronment so that every hospital has a copy of recorded medical data. Multi user rest server provided by Hyperledger framework is used to prevent unauthorized user accessing stored medical data inside the blockchain. Data availability can be maintained because blockchain keeps a copy of data on each peer. Data privacy can be maintained by using multi user rest server and access control provided by Hyperledger framework. Data integrity can be maintaned because blockchain used consensus mechanism. Performance results on this research shows that increased latency metrics directly proportional to the number of users accessing data inside the blockchain.